Re-calibrate - Nadirah Abdul Razak (2014)
This project presents pseudo-functional inventions meant to help camouflage the urban street artist while also enabling the act of urban art-making to move into new realms of performance. Inventions include wearables, tools, weapons and accessories all tailored to the actively invisible urban mark maker.